Unrelated Donor Cord Blood Transplantation in Children: Lessons Learned Over 3 Decades. (30th January 2023) - Kurtzberg, Joanne; Troy, Jesse D; Page, Kristin M; El Ayoubi, Hanadi Rafii; Volt, Fernanda; Maria Scigliuolo, Graziana; Cappelli, Barbara; Rocha, Vanderson; Ruggeri, Annalisa; Gluckman, Eliane
Abstract: Four decades ago, Broxmeyer et al. demonstrated that umbilical cord blood (CB) contained hematopoietic stem cells (HSC) and hypothesized that CB could be used as a source of donor HSC for rescue of myeloablated bone marrow. In 1988, Gluckman et al. reported the first successful matched sibling cord blood transplant (CBT) in a child with Fanconi Anemia. In 1991, Rubinstein et al. established an unrelated donor CB bank, and in 1993, the first unrelated CBT used a unit from this bank. Since that time, >40 000 CBTs have been performed worldwide. Early outcomes of CBT were mixed and demonstrated the importance of cell dose from the CB donor. We hypothesized that improvements in CB banking and transplantation favorably impacted outcomes of CBT today and performed a retrospective study combining data from Eurocord and Duke University in 4834 children transplanted with a single unrelated CB unit (CBU) from 1993 to 2019. Changes in standard transplant outcomes (overall survival [OS], disease free survival [DFS], acute and chronic graft-versus-host disease [GvHD], treatment related mortality [TRM], and relapse) over 3 time periods (1: <2005; 2: 2005 to <2010; and 3: >2010 to 2019) were studied. Increased cell dose and degree of HLA matching were observed over time. OS, times to engraftment, and DFS improved over time. The incidence of TRM and GvHD decreased while the incidence of relapse remained unchanged. Relative contributions of cell dose and HLA matching to transplant outcomes were also assessed and showed that HLA matching was more important than cell dose in this pediatric cohort. Graphical Abstract: